Freshwater and sediment data of the entire Weser river and its tributaries sampled during summer 2016 - Pröfrock, Daniel; Zimmermann, Tristan; Irrgeher, Johanna; Pieper, Andrea; Erbslöh, Hans-Burkhard; Dutschke, Florian (PANGAEA, 2022)
A key task in understanding and mapping the complex mass transport pathways and potential transformation processes of contaminants in coastal regions such as the German Bight is to determine and evaluate the most significant contribution sources into coastal areas. Rivers represent one key input source within this context. As part of a river campaign in June 2016, sediment and freshwater samples were taken from the Weser river and its tributaries to identify their elemental and isotopic fingerprint and to investigate potential inputs to the German Bight.